2020
DOI: 10.1007/s40123-020-00271-9
|View full text |Cite
|
Sign up to set email alerts
|

Less-Lethal Weapons Resulting in Ophthalmic Injuries: A Review and Recent Example of Eye Trauma

Abstract: Introduction: Prior reports have highlighted the dangers of crowd control weapons such as rubber bullets, paintball guns, and pepper spray. Many of these reports were written decades ago and outside of the USA. We summarize a review of the literature and discuss a contemporary case of a ruptured globe and facial trauma secondary to a projectile weapon. This case serves to highlight the severity of eye trauma caused by less-lethal weapons; severe morbidity or even mortality can occur. Clinical Description: A ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…Um estudo retrospectivo sobre lesões oftálmicas causadas por armas não letais demonstrou que de 43 casos, 25 resultaram em fraturas orbitárias e rompimento de globo ocular (Ifantides et al, 2020). Outro estudo realizado no Chile, demonstrou que dentre 182 casos suspeitos de trauma ocular por balas de borracha 33 evoluíram com amaurose e 90 exibiram deficiência visual grave (Rodriguez et al, 2020).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Um estudo retrospectivo sobre lesões oftálmicas causadas por armas não letais demonstrou que de 43 casos, 25 resultaram em fraturas orbitárias e rompimento de globo ocular (Ifantides et al, 2020). Outro estudo realizado no Chile, demonstrou que dentre 182 casos suspeitos de trauma ocular por balas de borracha 33 evoluíram com amaurose e 90 exibiram deficiência visual grave (Rodriguez et al, 2020).…”
Section: Discussionunclassified
“…A cápsula que a envolve geralmente é constituída por propelente de pólvora e espoleta (Cruz, 2018). As dimensões desses projéteis podem variar de 3,5cm a 9,15cm, pesar entre 135 a 140g e ultrapassar a velocidade de 70m/s (Ifantides et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…1 More recently, Ifantides et al describe a case of globe rupture likely caused by a foam round during the 2020 George Floyd protests. 2 A meta-analysis showed that 85% of all KIP-related ocular injuries globally resulted in permanent blindness. 3% of all KIP-related injuries resulted in death.…”
Section: Discussionmentioning
confidence: 99%
“…Aircraft, vehicle, and drone-guided technologies are also used as delivery systems. Additionally, non-lethal projectile weapons have a high risk of inducing severe traumatic injuries when fired at a person ( Ifantides et al, 2020 ).…”
Section: Delivery Systems Of Riot Control Agents (Rcas)mentioning
confidence: 99%